2019
DOI: 10.1101/737742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosomal Mcm2-7 distribution is the primary driver of the genome replication program in species from yeast to humans

Abstract: The spatio-temporal program of genome replication across eukaryotes is thought to be driven both by the uneven loading of pre-replication complexes (pre-RCs) across the genome at the onset of S-phase, and by differences in the timing of activation of these complexes during Sphase. To determine the degree to which distribution of pre-RC loading alone could account for chromosomal replication patterns, we identified the binding sites of the Mcm2-7 helicase complex, a key component of the pre-RC that is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
3
7
0
Order By: Relevance
“…Our combination of MCM ChIP-seq and replication timing data also allow us to directly confirm in a single experiment previous conclusions, drawn from comparing data collected in different studies, that replication timing correlates with levels of MCM loading (Das et al, 2015;Foss et al, 2020). Although the correlation between MCM levels and replication timing is robust (Figure 4c, p > 10 -5 ), it is clearly not the only determining factor (r = 0.29-0.52).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our combination of MCM ChIP-seq and replication timing data also allow us to directly confirm in a single experiment previous conclusions, drawn from comparing data collected in different studies, that replication timing correlates with levels of MCM loading (Das et al, 2015;Foss et al, 2020). Although the correlation between MCM levels and replication timing is robust (Figure 4c, p > 10 -5 ), it is clearly not the only determining factor (r = 0.29-0.52).…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, in a multiple-MCM scenario, more than one MCM double-hexamer complex can be loaded at a single origin, so MCM occupancy can range from 0 to many. Both single-and multiple-MCM scenarios have been proposed (Das et al, 2015;Foss et al, 2020;de Moura et al, 2010;Das and Rhind, 2016;Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data points to a model where the more MCMs that are available for activation at an origin in S phase, the higher the likelihood that the specific origin will initiate early. Indeed, this MCM-stoichiometry model fits well with kinetic modeling of replication, which predicts that stochastic firing arising from differences in the availability of MCM in the presence of limiting initiation factors can give rise to the observed replication kinetics seen in budding yeast cells [ 21 , 22 , 26 ]. It is important to note that the MCM-stoichiometry models are equally valid whether MCM stoichiometry varies from 0 to 1 or 0 to many.…”
Section: Discussionmentioning
confidence: 58%
“…Although excess loading of MCM is important for a successful S phase under conditions of replication stress, it has also been implicated in contributing to the replication timing program under normal conditions. Genome-wide MCM mapping experiments in budding yeast have shown that MCM is loaded at origins in different amounts, and that the level of MCM loading correlates with the time in S phases at which an origin fires [ 20 , 21 ]. In addition, mutation of the B2 element in ARS1, which has been shown to be important for MCM loading at that origin, causes reduced MCM loading and a delay in replication timing [ 20 , 54 ].…”
Section: Discussionmentioning
confidence: 99%